(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
In the article in higher education In higher education, the Annotal Teacher’s importance is important in the course of today’s education, modernization processes, globalization processes for innovative society, training specialists, training, training systems, pedagogical activity, to modernize the efficiency of pedagogical activities